Description of a new species of Neocollyris W. Horn, 1901 (Coleoptera Cicindelidae) with a detailed description of the larval development observed In Situ on a native non-endemic Premna odorata Blanco (Lamiaceae) in the Philippines - Medina, Milton Norman D. (Philippine Journal of Science, 2023)
This paper presents Neocollyris (Neocollyris) anichtchenkoisp. nov., a new species of Neocollyris W. Horn, 1901 (Coleoptera: Cicindelidae) from Luzon Island, Philippines. Larval development was documented in situ in Premna odorata Blanco (Lamiaceae). Scanning electron micrograph images of the larvae are also provided. This is the first record of a new species with notes on the larval development of a Philippine endemic Neocollyris.